Bioreduction of hexavalent chromium on goethite in the presence of Pseudomonas aeruginosa. (October 2020) - Li, Yihao; Wang, Huimin; Wu, Pingxiao; Yu, Langfeng; Rehman, Saeed; Wang, Junfeng; Yang, Shanshan; Zhu, Nengwu
Abstract: The effective mineral absorption and bioreduction were considered as two preferred processes to alleviate the bioavailability and toxicity of toxic trace metals. In this study, the bioreduction of hexavalent chromium (Cr(VI)) on goethite (FeOOH) in the presence of Pseudomonas aeruginosa ( P. aeruginosa ) was investigated with different environmental factors, including carbon source concentrations, pH, temperature and initial Cr(VI) concentrations. The characterization of FeOOH– P. aeruginosa indicated that P. aeruginosa was surrounded by FeOOH, which could provide the essential iron for bacterial growth and reduce Cr(VI) to Cr(III). The optimal experimental conditions for Cr(VI) (initial concentration: 35 mg L −1 ) absorption (∼46%) and bioreduction (∼54%) involved a temperature of 45 °C and pH of 5.5. Meanwhile, extracellular polymeric substances (EPS) secreted by P. aeruginosa and its functional groups played important roles in the reduction of Cr(VI). They could reduce Cr(VI) to Cr(III) and transform to Cr(OH)3 or Fex -Cr(1-x) (OH)3 precipitation. These results of this study are of significant importance to better understand the environmental geochemical behavior of Cr(VI) with the interactions between soil minerals and microorganisms. Graphical abstract: Image 1 Highlights: Goethite can reduce the toxicity of Cr(VI) to Pseudomonas aeruginosa ; . Extracellular Polymeric Substances play an important role in Cr(VI) reduction. The reduction products of Cr(VI) by goethite- Pseudomonas aeruginosa complexes mainly exist as metal complexes.